Methanol fixation and tagmentation of RNA/DNA hybrids directly enable single-cell transcriptome sequencing - Xu, Tao; Xu, Yicong; An, Ziyang; Li, Yiheng; Yang, Jiawen; Zhang, Weixing; Xu, Jin (Frontiers in Genetics, 2025)
ObjectiveSingle-cell transcriptome sequencing is a powerful tool for investigating cellular diversity in normal development and disease. However, prevalent methods predominantly employ 3′-end sequencing of transcripts, limiting the analysis of alternative splicing and other post-transcriptional processes. While full-length single-cell transcriptome sequencing methods, such as Smart-seq, offer more comprehensive information, but are restricted by low-throughput. To overcome these limitations, we propose a strategy that combines in situ reverse transcription and transposition with a high-throughput micro-fluid platform to enable scalable full-length transcriptome profiling at single-cell resolution.MethodsIn this study, we utilized methanol fixation on cultured cells to evaluate RNA integrity and cellular preservation post-fixation. In situ reverse transcription followed by RNA/DNA hybrids transposition was performed to test the efficiency of these reactions. The transposed fragments were sequenced and investigated to determine transcriptome capture efficiency. Finally, we combined in situ reactions with the 10X Genomics scATAC-seq platform to prepare a single-cell transcriptome library, aiming to assess the feasibility of full-length transcriptome sequencing at the single-cell level using this combined approach.ResultsMethanol fixation enables preservation of RNA and facilitates in situ reverse transcription of full-length cDNA. Importantly, cells maintain their integrality after reverse transcription and transposition even under low concentration of methanol. Reducing the methanol concentration to 40% further enhances transcript capture efficiency. At the single-cell level, this strategy enables the capture of full-length transcriptomes, demonstrating a great potential for application in single-cell sequencing.